Oposições múltiplas: abordagem contrastiva para sujeitos com desvio fonológico - Ceron, Marizete Ilha (2009)
This research aims at applying and testing the Multiple Oppositions Approach (Williams, 2000a) of children of Brazilian Portuguese speakers with degrees of phonological disorder. The studied group was composed by 5 subjects, 2 males and 3 females, with average age in the beginning of treatment 6:1. It was carried out phonological and complementary assessments. The speech data were collected and analyzed through the phonological assessment before and after the treatment. After the assessment, the subjects were submitted to the therapy using the Multiple Oppositions Approach (Williams, 2000a) during 25 sessions. It was analyzed the therapeutic progress when referring to the phonetic inventory and phonological, to the distinctive features focused during the therapy by the target sound, as well as changes in the percentage of consonants correct-revised (PCC-R) and kinds of generalization (to lexical items non used during treatment, to another position of the word, inside a sound class and to other sound class). It was verified a statistically significant increase on the number of sounds in the phonetic inventory, on the acquired phonemes in the phonological inventory, with a statistically significant decrease in the number of changed distinctive features. There was a statistically significant difference to the PCC-R and some kinds of generalization (to lexical items none used during treatment, to another position of the word and to other sound class). There was no statistically significant difference inside a sound class; however it was observed an increase in the final assessment percentage. Thus, it was concluded that the Multiple Oppositions Approach was effective for the treatment of subjects of Brazilian Portuguese speakers because the model provided changes in the number of sounds in the phonetic inventory, of acquired phonemes in the phonological inventory, one increase no PCC-R and all the kind of generalizations (to lexical items non used during treatment, to another position of the word, inside a sound class and to other sound class). The subjects who added more phonemes to their phonological inventory were the ones who had a decrease in the number of changed distinctive features.